Biophysical characterisation of Dacryodes edulis fruits from three markets in Cameroon - Atangana, A.R.; Asaah, E.; Tchoundjeu, Z.; Awono, A.; Schreckenberg, Kate; Leakey, R.R.B. (Presses Universitaires d'Afrique, 2002)
Studies were done in order to assess variation in fruit size and weight, nut size and weight and determinate relationships between these characteristics and price using 149 samples of Dacryodes edulis fruits from three markets at the peak of season in Cameroon. 50 samples per market in two markets (Mfoundi market [Yaonde] and Makenene centre market) and 49 samples in Makenene East market were bought randomly from traders. The measurement of 10 characteristics of 24 fruits per sample identified significant variation in fruit size and weight and nut weight in each market. Fruit price was found to vary with flesh mass, fruit mass and fruit size in retailers markets while wholsalers don't take into account fruit variability. In contrast, pulp price per kg was negatively correlated with flesh weight in wholesalers' markets. The most frequent skin colour was "georgetown lime" (29A7 in the Methuen colour code) and the most frequent flesh colour was violet (18D6 in the Methuen colour code). From this study, Dacryodes edulis fruit ideotype fetching highest price in the retailers markets is characterized by length, flesh and fruit mass and white skin colour.